2014
DOI: 10.4314/ajtcam.v11i3.40
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity-Guided Isolation of Anticancer Agents from <i>Bauhinia Kockiana</i> Korth.

Abstract: Background: Flowers of Bauhinia kockiana were investigated for their anticancer properties. Methods: Gallic acid (1), and methyl gallate (2), were isolated via bioassay-directed isolation, and they exhibited anticancer properties towards several cancer cell lines, examined using MTT cell viability assay. Pyrogallol (3) was examined against the same cancer cell lines to deduce the bioactive functional group of the phenolic compounds. Results:The results showed that the phenolic compounds could exhibit moderate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Another study investigated hesperidin impact on the proliferation of MCF-7 human breast cancer cells, and prostate cancer cells [31]. On the other hand, pyrogallol, a major phenolic compound identified from V. faba exhibited a moderate effect against prostate cancer cell in a previous study Chew et al [32] Catechol which is another significant phenolic identified from P. sativum apparently turned out to have a sensible effect on two breast cancer cell lines (MCF-7 and MDA-MB-231 [33]. q-Hydroxy benzoic acid, a phenolic acid present in P. sativum and V. faba with great amounts was previously proven to have strong cytotoxic activity on both colon (HCT116) and liver (HEPG2) carcinoma cell line [34].…”
Section: Discussionmentioning
confidence: 99%
“…Another study investigated hesperidin impact on the proliferation of MCF-7 human breast cancer cells, and prostate cancer cells [31]. On the other hand, pyrogallol, a major phenolic compound identified from V. faba exhibited a moderate effect against prostate cancer cell in a previous study Chew et al [32] Catechol which is another significant phenolic identified from P. sativum apparently turned out to have a sensible effect on two breast cancer cell lines (MCF-7 and MDA-MB-231 [33]. q-Hydroxy benzoic acid, a phenolic acid present in P. sativum and V. faba with great amounts was previously proven to have strong cytotoxic activity on both colon (HCT116) and liver (HEPG2) carcinoma cell line [34].…”
Section: Discussionmentioning
confidence: 99%
“…Voucher specimen (MUM-LEGUM-001) was deposited in the herbarium of School of Science, Monash University Malaysia. The extraction of flowers was performed as according to Chew et al [ 13 ] with slight modifications. Fresh flowers of B. kockiana (1.7 kg), were collected and washed with distilled water, then freeze-dried using a freeze dryer.…”
Section: Methodsmentioning
confidence: 99%
“…Bauhinia species are from Caesalpinioideae subfamily of Leguminosae. Bauhinia kockiana is a plant originates from Peninsular Malaysia but now it can also be found in the tropical forests of Thailand and Sumatra [ 13 ]. It is usually grown in the garden as ornamental plant because of its bright orange-red colour (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, herbal medicines can induce cell death by apoptosis, acting on initiation and tumor resistance [5]. In this context, species of the Bauhinia genus have shown activities on tumor progression stages [6][7][8]. Bauhinia variegata L. is a species of Asian origin, disseminated in the Brazilian territory, along with natural vegetation and in urban areas [9].…”
Section: Introductionmentioning
confidence: 99%